CD40L and Its Receptors in Atherothrombosis—An Update - Michel, Nathaly Anto; Zirlik, Andreas; Wolf, Dennis (Frontiers in Cardiovascular Medicine, 2017)
CD40L (CD154), a member of the tumor necrosis factor superfamily, is a co-stimulatory molecule that was first discovered on activated T cells. Beyond its fundamental role in adaptive immunity—ligation of CD40L to its receptor CD40 is a prerequisite for B cell activation and antibody production—evidence from more than two decades has expanded our understanding of CD40L as a powerful modulator of inflammatory pathways. Although inhibition of CD40L with neutralizing antibodies has induced life-threatening side effects in clinical trials, the discovery of cell-specific effects and novel receptors with distinct functional consequences has opened a new path for therapies that specifically target detrimental properties of CD40L. Here, we carefully evaluate the signaling network of CD40L by gene enrichment analysis and its cell-specific expression, and thoroughly discuss its role in cardiovascular pathologies with a specific emphasis on atherosclerotic and thrombotic disease.